ASSESSING SKF’S S&OP PROCESS: A CROSS-CASE ANALYSIS - Bergström, Adrian; Gustafsson, Hannes (My University, 2024)
The globalization of trade has significantly increased the complexity and vulnerability of supply chains. Major events like the COVID-19 pandemic, the Suez Canal blockage, and the Red Sea crisis have caused significant disruptions, highlighting the critical need for a robust Sales and Operations Planning (S&OP) process. To manage these risks effectively, companies must adopt a proactive approach to risk assessment and continuously evaluate and refine their S&OP process. This iterative approach ensures that the process remains effective and adaptable to changing conditions. The aim of this master’s thesis is to identify weaknesses and obstacles within SKF’s S&OP process by evaluating it with a maturity model. The maturity model also evaluates the S&OP processes of other organizations similar to SKF. A quantitative study was conducted, incorporating interviews, documentation, and a workshop. A cross-case study was also conducted to compare other companies’ S&OP processes and identify key similarities and differences with SKF’s S&OP process. Interviews and documentation formed the basis of the cross-case analysis, which was followed by a workshop. In the workshop, companies such as Alfa Laval, Getinge, Husqvarna, and Sandvik participated in open discussions about S&OP. In conclusion, SKF can improve their S&OP process by involving executive management and holding both pre-executive S&OP and executive S&OP meetings to assess and translate operational impacts into strategic actions. Appointing a process owner for coordination and implementing a planning hierarchy will ensure alignment between strategic goals and operational performance, fostering better company-wide coordination and decision-making.
Keywords: Sales and Operations Planning; Cross-case analysis; Strategic alignment; Planning levels